Designing global trade and logistics channels: a focus on the Chinese food and beverage market - Prataviera, Lorenzo Bruno; Melacini, Marco (Inderscience, 2023)
Internationalisation ventures entail a close relationship between the trade channel (TC) and the logistics channel (LC), but few studies address simultaneously TC and LC design. This study investigates how TC can influence LC design and explores the role played by related contextual factors. Abductive reasoning is adopted within middle-range purposes, elaborating previous theory with multiple case studies considering European food manufacturers tackling a specific empirical context (i.e. the Chinese food and beverage market). The study lends contingency theory elements and leverages them to develop nine propositions that can open to further inquiries about the influence of TC on LC design and the impact of the identified contextual factors. Moreover, it proposes the behavioural theory as a theoretical lens to approach LC (and not only TC) design. Lastly, it provides practitioners with insights that can be useful to improve their understanding of the Chinese food and beverage market.
Keywords: Global distribution channel design; Logistics channel; Trade channel; Food and beverage market; guanxi; multiple case studies